A Ten-year Retrospective Study of Tetanus at a Teaching Hospital in Bangladesh - Feroz, AHM; Rahman, Hafizur (Journal of Bangladesh College of Physicians and Surgeons, 2007)
Aims: To study the demographic, clinical features, treatment as well as outcomes of tetanus patients in the Bangladeshi population from 1994 to 2003. Design: A retrospective descriptive study. Setting: A large public Medical college hospital with a regional as well as referral service. Materials and Methods: All cases of tetanus in adult patients from January 1994 to December 2003 were identified from the medical record at the hospital and these were then retrospectively reviewed. Results: A total of 80 cases of tetanus were seen at the Faridpur Medical college hospital in the 10 years period with a mean of 8 cases per year. There were 55 male (68.75%) and 25 female (31.25%) patients. The mean age of the study population was 51.7±10.08 years. Most cases occurred in the age group of 60-69 years. Risk factor analysis revealed identifiable acute injury (puncture, prick/laceration) in 85%, CSOM (2.5%), surgery (2.5%), abortion (2.5%), skin ulcer (1.25%), burn (1.25%), child birth (1.25%), boil (1.25%). Thirty-two (40%) patients had medical wound care before hospital admission but none received tetanus immunoglobulin despite the absence of tetanus immunity. All the patients had the generalized type of disease. Body stiffness, trismus and dysphagia were the three commonest presenting complaints. All the patients with injury and wound (74/80) had their wound debrided. All the tetanus patients (80/80) received intravenous diazepam infusion as part of their management. Seventy two (90%) patients received intravenous crystalline penicillin. Sixty-five (81.25%) patients received intramuscular human antitetanus immunoglobulin and fourteen (17.5%) had tracheostomy performed. Inhospital complications were observed as respiratory (80%), cardiovascular (65%), gastrointestinal (57-5%), renal (33.37%), neurological (17.%) and others (22.5%). There were eighteen deaths in hospital, accounting for overall mortality of 22.5% (18/80). Higher mortality were observed in age group above 50 years than the age group below 50 years (29.16% vs 12.5%, P<0.05), in female than the male (40% vs 14.54%, P<0.05), in farmer than nonfarmer (30.95% vs 13.15%, P<0.05), in patients who had short incubation period than those who had incubation period more than one week (53.33% vs 23.25%, P<0.05). Conclusion: In general, tetanus remains in Bangladesh an important disease with substantial mortality that primarily affects unvaccinated or inadequately vaccinated individuals. Prevention during wound management of tetanus prone wounds was inappropriate in many patients. The elderly population may have the highest risk for tetanus since they may not have had tetanus toxoid immunization or regular booster injections. It is, however, highly preventable through both routine vaccination and appropriate wound management. Our case series show comparable pattern and outcome with other case series in the developing countries reported in the literatures. (J Bangladesh Coll Phys Surg 2007; 25 : 62-69)